Government Debt and Long-Term Interest Rates - Kinoshita, Noriaki (IMF Working Papers; Working Paper ;, 2006)
This paper examines the relationship between government debt and long-term interest rates. A dynamic general equilibrium model that incorporates debt nonneutrality is specified and solved, and numerical simulations using the model are undertaken. In addition, empirical evidence using panel data for 19 industrial countries is examined. The estimation provides some evidence supporting the theoretical predictions: the paper finds that the simulated and estimated interest rate effects of government debt tend to be small. However, an increase in government consumption and debt leads to a considerably larger effect. The paper also argues that, although the interest rate effects of pure crowding out may be limited, the economic impact of accumulating government debt cannot be ignored.